Chocó entre la Corrupción y el Olvido (2020)
In this article, the topic to address aspects to be found economically in the Chocó department. From a local, regional and territorial level, to achieve a suitable development of this article, a compilation of various theories will be carried out, in order to identify and define each of the phases in which various alternatives would be proposed in order to be able to achieve sustainable development.